The effect of barbiturates in porphyria turcica - Doğramacı, İhsan; Özand, Pınar; Müftü, Yunus; Ergene, Turhan (The Turkish Journal of Pediatrics, 1963)
Case histories of three patients with porphyria turcica are presented. Two patients manifested the disease in a quiescent state, one was acutely ill. All three volunteered for experimental treatment with a porphyria-inducing drug: seconal, an allylbarbiturate. In no case did the drug aggravate existing symptoms or induce new ones nor did it produce any change in the excretory pattern of porphyrins.The biochemical pathology of the drug-induced porphyrias, in particular the effect of the barbiturate analogue, sedormid, on porphyrin metabolism, is discussed in some detail.